ANALISA PENGARUH PAJAK DAERAH DAN RETRIBUSI DAERAH TERHADAP PENDAPATAN ASLI DAERAH KOTA TANGERANG SELATAN - Asep Mulyana (Jurnal Akuntansi Bisnis dan Ekonomi, 2018)
This research method using descriptive and verification method. The descriptive method aims to test a fairly clear picture of the object under study and draw conclusions based on research conducted. While research method verification aims to estimate (estimate) and hypothesis testing (testing hypothesis). In testing the hypothesis author using the t-test for the hypothesis of partial and simultaneous F test for the hypothesis. While statistical tools such as regression, correlation, and a determination made through SPSS for Windows 20.0, by first doing a classic assumption test including normality test, autocorrelation, multicollinearity, and heteroscedasticity.